AN OVERVIEW OF THE METHOD, MANAGEMENT, PROBLEM AND THEIR SOLUTION IN THE PEARL OYSTER (Pinctada margaritifera) CULTURE - ludi Aji (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Pearl culture operations can be divided into three categories which are collection/hatchery production, ongrowing and pearl culture. For the hatchery, the pearl oyster industry relies on spat collection at natural production atolls where spat is abundant during the warm season and also from broodstock in the laboratory condition. After that, hatchery grown juveniles are put into the sea on the material which they settle upon. The spat are left to grow for 2 years till an average size of 90 mm. Pearl culture involves the implantation of a spherical nucleus together with a piece of mantle tissue (Saibo) from a sacrificial oyster, into the gonads. Although pearl culture is extensive with little control over weather, the use of good management methods can drastically increase productivity and result in higher profitability. Therefore, management of culture system such as site selection, settlement, feeding, stocking density and pearl culture technique is essential. For example, site selection is the most critical factor affecting pearl oyster productivity and spat collection, as the oysters spend most of their growing time exposed to water elements. Site selection must take into account important water quality parameters like temperature, salinity and turbidity. Moreover, it was identified several problems in pearl oyster culture including predation, disease and biofouling. They can result in massive loss in productivity. However, pearl industries have solution to deal with those problems. For instance, it can be done by cleaning mesh bag, biofouling organisms and pearl oyster regularly. For the future, the genetic approach like to create faster growing oysters, resistance to diseases and production of higher quality pearls has given promising results. Therefore, the productivity of pearl oyster can be improved.